(untitled) (Comprehensive Journal of Science, 2025)
This study aims to enable pupils at certain Azzawia school , understand the subjects by their own strategy of learning also, examine the main problems that faced the teachers using learning strategies. The study is restricted to the most frequent problems encountering the pupils understanding via their own way of learning. More precisely, the concentration be on the usage of the learning strategies, since they are considered very problematic. The study takes place in place in Zameet School at Azawia City , during the fall 2024. The sample of the study are 50 pupils in the 5th year of primary school. Three main instruments, pilot study, pre and post tests and a suggestion course that is, the researcher used a pilot study as well to confirm the existence of the problem. The students were divided into two groups, experimental and control. The pretest was conducted to evaluate the students’ learning strategies, whereas the posttest was to check the students’ improvement after the suggested course that the researcher implemented. The pretest marks were compared to the posttest marks for both groups. The students written products were then analyzed by using error analysis approach in order to review the most frequent errors in using learning strategies. The findings confirmed the hypothesis that the pupils at Zawia City faced difficulties in the performance and usage knowledge of learning strategies.